Central Versus Peripheral Cardiovascular Risk in Metabolic Syndrome - Edgell, Heather; Petrella, Rob; Hodges, Gary J.; Shoemaker, J. K. (Frontiers in Physiology, 2012)
Individuals with metabolic syndrome (MetS; i.e. 3 of 5 of the following risk factors (RFs): elevated blood pressure, waist circumference, triglycerides, blood glucose or reduced HDL) are thought to be prone to serious cardiovascular disease and there is debate as to whether the disease begins in the peripheral vasculature or centrally. This study investigates hemodynamics, cardiac function/morphology, as well as mechanical properties of the central (heart, carotid artery) and peripheral (total peripheral resistance, forearm vascular bed) vasculature in individuals without (1-2 RFs; n=28), or with (≥3 RFs; n=46) MetS. After adjustments for statin and blood pressure medication use, those with MetS had lower mitral valve E/A ratios (<3 RFs: 1.24±0.07; ≥3 RFs: 1.01±0.04; P=0.025), and higher total peripheral resistance index (<3 RFs: 48±2 mmHg/L/min/m2; ≥3 RFs: 53±2 mmHg/L/min/m2; P=0.04). There were no differences in heart size, carotid artery measurements, cardiovagal baroreflex sensitivity, pulse wave velocity, stroke volume index, or cardiac output index due to MetS after adjustments for statin and blood pressure medication use. In a separate analysis, the use of statins was associated with increased inertia in the brachial vascular bed, increased HbA1c and decreased LDL cholesterol. The independent use of anti-hypertensive medication was associated with decreased predicted VO2max, triglycerides, diastolic blood pressure, interventricular septum thickness, calculated left ventricle mass, left ventricle posterior wall thickness, and left ventricle pre-ejection period, but increased carotid stiffness, HDL cholesterol, and heart rate. These data imply that both a central cardiac effect and a peripheral effect of vascular resistance are expressed in MetS. These data also indicate that variance in between-group responses due to pharmacological treatments are important factors to consider in studying cardiovascular changes in these individuals.